Reproductive Health and Service Delivery Status in a Rural Area of Bangladesh (Bangladesh Journal of Obstetrics & Gynaecology, 2013)
Background: Reproductive Healthcare Services is a service that contributes to reproductive  health and wellbeing through preventing and solving reproductive health problems.Objective of the Study: To find out the reproductive health status and also the service  delivery pattern in a rural area.Methodology: It is a cross sectional study done in a village named Kalirbazar, 3km away  from the BARD, Comilla, during the period of13th February to 13th March, 2011. Data were  collected purposively by Individual interview through a structured questionnaire. A total 30  women of reproductive age group (15-45yrs) were taken. Both adolescent unmarried girls and  married women of reproductive age group were included in this study. After collection, data  were analyzed, tabulated and presented.Results: Respondents were mostly married( 63%), unmarried 33%; almost all of the women were Muslim (93%) and from low socioeconomic status(77%). Sixty six percent of women got  married before 18 yrs of age and 47% were illiterate, more than half of the women (60%) were  housewives and 28% dropped out from schools. Forty percent of married women had 2-3  children.Most of the Women had knowledge about contraception, like-OCP (33%), inj. (27%),  barrier (17%), female sterilization (06%) and 17% had no knowledge. Among the married  women 53% use OCP, 32% injectable contraceptives, 11% sterilization and 04% had  vasectomy. Among respondents, 70% had some sorts of menstrual problem, 85% women  lacked of antenatal checkup, 95% delivery occurred at home, 90% delivery conducted by  local dhai and unexpectedly 73% of women had knowledge of STD/HIV&AIDS. 60% of the  women got the information related to reproductive health from relatives and also from media,  health care provider. Most of the women (87%) said that whatever the health service status;  there were problems in getting the services. Only few of them were satisfied with the services  getting either from GO or NGO or from private sector. Almost all the women were buying the  reproductive healthcare services (83%).Conclusion: Reproductive health status in the rural area is not at all satisfactory. GO. and  NGO often fail to make health services available to the doorstep of the users in the community  who are in dire need of it . DOI: http://dx.doi.org/10.3329/bjog.v26i1.13756 Bangladesh J Obstet Gynaecol, 2011; Vol. 26(1) : 27-30